Ion properties from high-L Rydberg atom spectroscopy: applications to nickel - Woods, Shannon L., author; Lundeen, Stephen R., advisor; Krueger, David A., committee member; Gelfand, Martin P., committee member; Krummel, Amber T., committee member (Colorado State University. Libraries, 2012)
An effective potential model describing high-L Rydberg states was systematically derived. The model assumes that the response of the core ion to the electric field of the Rydberg electron is at least approximately adiabatic; in other words, the excitation energies of the core ion are large compared to the typical energies of the Rydberg levels. The resulting model should describe a wide variety of high-L Rydberg systems. It can be used, in combination with experimental measurements of fine structure patterns, to extract measurements of core ion properties that control long-range interactions between the core and the Rydberg electron. These include permanent electric and magnetic moments, and electric polarizabilities. As an example application of the model, the fine structure pattern in n = 9 Rydberg levels of nickel was measured using the Microwave Resonant Excitation Stark Ionization Spectroscopy (RESIS) method. Properties of the 2D5/2 ground state of Ni+ extracted from these measurements include quadrupole and hexadecapole moments Q = -0.4705(2) a.u. and ∏ = 0.27(9) a.u., scalar and tensor dipole polarizabilities αD,0 = 7.925(10) a.u. and αD,2 = 1.043(33) a.u., and scalar quadrupole polarizability αQ,0 = 71(9) a.u. In addition, evidence for a permanent magnetic octupole moment of Ni+ was seen, parameterized by the coefficient CM3 = -0.346(57) a.u.
Keywords: effective potential model; resonance ionization spectroscopy; Rydberg states